(untitled) (Global Journal of Advanced Engineering Technologies and Sciences, 2018)
Automobile engine inner Cylinder Thermal Cycle is fiercely connected with the second thermal theory, and obviously there is direction feature while the energy is exchanging with each other, for instance, mechanical energy is able to exchange into thermal energy entirely, and the theoretical efficiency is approaching 100 percent. This sort of infinity exchangeable energy is called ‘exergy’, machinery energy is exergy entirely. For these reasons, in habit, ‘valid work’ is as same as ‘infinity exchangeable energy’. However, reversely exchange from thermal to mechanical energy isn’t entire yet, the exchange ability is limited by the second thermal theory. Therefore, from the technical and economical views, the quality of first one is higher, and more valuable. This thesis is mainly on the contrasts of several cycles’ exergy